The Relationship of the Green Lawrence Theory of Exclusive Assessment and Stunting Events in Busungbiu Puskesmas I Buleleng District of Bali - Ni Kadek Shinta Marheni (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Stunting is a chronic condition that describes stunted growth due to long-term malnutrition, indicated by a TB / U z-score of less than -2 SD. Stunting data at the Pusung Busungbiu in 2019 was 51.25% so research on the factors causing stunting was needed. Method: This study was an observational analytic study with a case control approach. The total sample of 200 people included mothers and toddlers aged 24 - 59 months according to inclusion criteria. Sampling is done by using cluster random sampling to select groups of samples and simple random sampling to select samples. The independent variables of this study were maternal height, sex of the toddler, age of the toddler, family income, parent's education, mother's married age, history of maternal KEK status, history of birth weight, long history of birth, history of exclusive breastfeeding and history of time of giving MP ASI. The collected data was tested using Chi Square and multiple logistic regression to find out the significant level at the significance level a = 0.05. Results: The results of multivariate analysis showed that birth length <48 cm had (P = 0.00; OR 14.1) and the age group 24-36 months had (P = 0.01; OR 1.6) while maternal height, toddler sex, family income, parent's education, mother's married age, history of maternal KEK status, history of birth weight, history of exclusive breastfeeding and history of time of giving ASI MP are not factors causing stunting. Conclusion: Birth length <48 cm and age groups 24-36 months were the most dominant causes of stunting. So it is necessary to get interventions, assistance and monitoring of growth and development that is good to improve the quality of life in the future